Influence of Islamic Philosophy on the Faith and Practices of Patients with Diabetes Mellitus and Its Musculoskeletal Manifestations - Mohd Khairul Zul Hasymi Firdaus; Urai Hatthakit; Waraporn Kongsuwan; Muhammad Kamil Che Hasan (Fakultas Ilmu Keperawatan Universitas Indonesia, 2020)
Transcultural care is an important aspect of patient care. This review paper discusses the influence of Islamic philosophy on the faith and practices of Muslim patients with diabetes mellitus and its musculoskeletal manifestations. Relevant articles were searched from the electronic databases Cumulative Index of Nursing and Allied Health Literature, PubMed, ProQuest, and Science Direct using the keywords “Islamic philosophy, the influence of Islamic Philosophy in Muslim patients, religious practice during sick, fasting months, and sick.” No time limitation was specified for article selection. The database search yielded 170 potential articles. The abstracts of these articles were screened, and 50 full-length manuscripts were obtained, reviewed, and analyzed for their relevance to the subject matter. Discussions rooted in the ontology, epistemology, and methodology of Islamic philosophy were described in detail to provide a sound understanding of its influence on Muslim patients. The ontology of Islamic philosophy is based on four important concepts, namely, the Unity of Allah, the Unity of Creation, the Unity of Thought, and the Unity of Man. The epistemological approach can help Muslim patients search for knowledge on the basis of ontology and three principles, namely, Ilm’ Yaqin, Ainul Yaqin, and Haqqal Yaqin. The ontology and epistemology shape the methodology of Muslim patients’ daily life according to the Islamic concepts of the Five Pillars and Six True Faiths. The issues patients with diabetes mellitus and its musculoskeletal manifestations encounter usually arise when they need to perform obligations during fasting and prayers. Understanding Islamic philosophy in caring for patients with diabetes is important among healthcare professionals to provide appropriate care. Better healthcare services may be provided to Muslim patients if their specific needs are fulfilled according to their beliefs and culture. Abstrak Filosofi Islam Memengaruhi Iman dan Praktek Klien dengan Diabetes Mellitus dan Manifestasi Muskuloskeletalnya: Review. Perawatan transkultural adalah aspek penting ketika memberikan perawatan kepada klien. Artikel tinjauan ini akan membahas tentang filsafat Islam yang memengaruhi keyakinan dan praktik klien diabetes Muslim. Artikel yang relevan dicari dari database elektronik Cumulative Index of Nursing and Allied Health Literature (CINAHL), PubMed, ProQuest, dan Science Direct. Kata kunci yang digunakan 'filsafat Islam, pengaruh Filsafat Islam pada klien Muslim, praktik keagamaan selama sakit, bulan puasa, dan sakit'. Tidak ada batasan waktu pada pemilihan artikel. Pencarian database mengidentifikasi sejumlah 170 artikel. Abstrak disaring dan 50 artikel lengkap diperoleh, ditinjau, dan dianalisis jika relevan. Diskusi rooting pada ontologi, epistemologi, dan metodologi filsafat Islam dijelaskan secara rinci untuk memahami pengaruhnya terhadap klien Muslim. Ontologi filsafat Islam didasarkan pada empat konsep penting; Kesatuan Allah, Kesatuan Ciptaan, Kesatuan Pemikiran, dan Kesatuan Manusia. Pendekatan epistemologis membantu klien Muslim untuk mencari pengetahuan berdasarkan ontologi dan tiga prinsip (Ilm Ya Yaqin, Ainul Yaqin, dan Haqqal Yaqin). Ini telah membentuk metodologi klien Muslim dalam kehidupan sehari-hari berdasarkan pada Islam Lima pilar dan Enam Iman Sejati. Masalah klien dengan diabetes mellitus dan manifestasi muskuloskeletalnya biasanya muncul setiap kali melakukan kewajiban saat puasa dan berdoa. Kebutuhan mereka untuk mengamati kepatuhan pengobatan, kontrol diet, doa sehari-hari, dan bagaimana metodologi memengaruhi kehidupan sehari-hari mereka. Pemahaman filosofi Islam dalam merawat klien diabetes adalah penting di antara para profesional kesehatan untuk memberikan perawatan yang tepat. Diharapkan bahwa layanan kesehatan yang lebih baik untuk klien Muslim jika kebutuhan spesifik keyakinan dan budaya terpenuhi. Kata kunci: diabetes mellitus, filsafat Islam, manifestasi muskuloskeletal, Muslim